Protein Ontology Project: 2007 - Sidhu, Amandeep; Dillon, Tharam S.; Chang, Elizabeth (WIT Press, 2007)
Protein Ontology (PO) provides integration of heterogeneous protein andbiological data sources. PO converts the enormous amounts of data collected bygeneticists and molecular biologists into information that scientists, physiciansand other health care professionals and researchers can use to easily understandthe mapping of relationships inside protein molecules, interaction between twoprotein molecules and interactions between protein and other macromolecules atcellular level. This paper discusses the updates that happened to ProteinOntology Project since it was last presented at Data Mining 2006 Conference.